Development of Interactive Story Book For Ecoliteration Learning to Stimulate Reading Interest in Early Grade Students Elementary School - Hendratno Hendratno; Yoyok Yermiandhoko; Fajar Nur Yasin (IJORER : International Journal of Recent Educational Research, 2022)
Research aims to produce a storybook containing ecoliteracy education for elementary school students of good quality in terms of the validity, practicality, and effectiveness of a product. This type of research is Research and Development with the ADDIE model. The instruments used were validation questionnaires, observations, teacher response questionnaires and learning outcomes tests. The results of this study indicate that the validation of interactive storybooks for ecoliteracy learning gets an average coefficient of validation from the validator, which is very valid qualifications. The practicality of loading the teacher's response questionnaire gets a percentage of 97%, the results of teacher and student observations get a percentage of 91% and 94%. The effectiveness based on giving pretest and posttest to students amounted to 30 students in grade 1 and 30 students in grade 2 with an average pretest result of 74, while the average posttest was 90.8. The result indicates that there is a significant difference in the learning outcomes of early grade elementary school students using interactive story books. Based on the validation of the instrument and the recapitulation of the questionnaire filled in by the teacher, it can be stated that the quality of the interactive storybooks developed are very valid, practical and effective for use in learning. This interactive storybook can help early grade elementary school teachers in growing interest in reading related to ecoliteracy learning so that students' awareness of caring for and caring for the surrounding environment can be carried out from an early age.